2016
DOI: 10.5604/17322693.1209211
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoblastoma Biology Using Isotope Ratio Mass Spectrometry: Utility of a Unique Technique for the Analysis of Oncological Specimens

Abstract: The prognosis in liver tumors cases in children may be challenging particularly because of the lack of versatile methods of its evaluation. Isotope ratio mass spectrometry allows one to determine the difference between hepatoblastoma histological subtypes and clearly indicates the cases with the best outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The head and neck cancers’ occurrence keeps rising so it is essential to establish if spectrometry, this new possibility of evaluation, can be as helpful as other types of diagnosing malignancies. Some studies have already indicated usefulness of IRMS in case of Wilms’ tumour, hepatoblastoma or rhabdomyosarcoma [ 19 , 22 , 32 ]. Numerous articles prove that, based on neoplasm’s isotopic composition and ratios, it is possible to picture its abnormal metabolism that reflects the course of the disease [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The head and neck cancers’ occurrence keeps rising so it is essential to establish if spectrometry, this new possibility of evaluation, can be as helpful as other types of diagnosing malignancies. Some studies have already indicated usefulness of IRMS in case of Wilms’ tumour, hepatoblastoma or rhabdomyosarcoma [ 19 , 22 , 32 ]. Numerous articles prove that, based on neoplasm’s isotopic composition and ratios, it is possible to picture its abnormal metabolism that reflects the course of the disease [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have already indicated usefulness of IRMS in case of Wilms’ tumour, hepatoblastoma or rhabdomyosarcoma [ 19 , 22 , 32 ]. Numerous articles prove that, based on neoplasm’s isotopic composition and ratios, it is possible to picture its abnormal metabolism that reflects the course of the disease [ 19 ]. A new method aimed at improving the process of staging may be a huge step forward in the assessment of the threat and towards winning our battle with the disease before it starts developing in an unstoppable manner…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It may also represent a potential source of data needed for the assessment of the most individual characteristics of cancer and complements those at the microscopic or molecular levels. Recently, a few preliminary studies have examined isotope ratios directly in tumour tissues [9, 10, 11, 12] with promising indications that isotopic composition may facilitate the classification of patients into risk groups [11, 12]. However, these previous studies have not covered all the prognostic parameters appropriate to the cancer type, which constitute the existing base for the choice of treatment protocol and prognosis in individual cases.…”
Section: Introductionmentioning
confidence: 99%